C# 6 and .NET Core 1.0 modern cross-platform development : create powerful cross-platform applications using C# 6, Net Core 1.0 ASP.NET Core 1.0 and Visual Studio 2015 /: create powerful cross-platform applications using C# 6, Net Core 1.0 ASP.NET Core 1.0 and Visual Studio 2015. (2016) - Price, Mark J
No abstract available